Health care : limits, laws, and lives at stake - Stevenson, Tyler (Tyler Dennis), 1988- (Hot topics (Lucent Press), 2019)
Offers a brief history of health care in the United States and discusses the debate surrounding health care reform. Includes discussion questions, a list of organizations to contact, and resources for further information.